Erenumab Impact on Sleep Assessed With Questionnaires and Home-Polysomnography in Patients With Migraine: The ERESON Study - Pellitteri, Gaia; Pez, Sara; Nilo, Annacarmen; Surcinelli, Andrea; Gigli, Gian Luigi; Lettieri, Christian; Valente, Mariarosaria (Frontiers in Neurology, 2022)
Introduction: Migraine and sleep share a complex and unclear relationship. A poor sleep may trigger migraine attacks; migraine, in turn, is frequently associated with sleep disorders. Few previous studies used questionnaires to assess sleep changes in patients treated with migraine-preventive medications. More extensive polysomnography-based studies for this purpose were not available. Objective: To investigate possible sleep changes in patients with migraine treated with erenumab, using validated sleep questionnaires and home-polysomnography. Methods: This observational, prospective, open-label pilot study was conducted at the Clinical Neurology Unit Headache Center of Udine University Hospital in 2020-2021. Patients were treated with erenumab as monotherapy or add-on treatment for migraine prevention. Sleep changes were evaluated with questionnaires and polysomnographic recordings at baseline, after three and 12 months of treatment. Erenumab efficacy and safety in migraine prophylaxis was also investigated. Results: Twenty-nine patients completed three months of follow-up, whereas 15 patients completed 12 months. We found a weak trend of improvement in daytime somnolence after three months of treatment, with stronger results after 12 months (median Epworth Sleepiness Scale score from 6.0 to 4.0, p = 0.015); a significant improvement in subjective sleep quality (median Pittsburgh Sleep Quality Index total score from 7 to 5; p = 0.001) was also observed. Home-polysomnography showed a significant increase in objective sleep efficiency, both after three (from 88.1 to 91.0, p = 0.006) and 12 months (from 87.1 to 91.0, p = 0.006) of treatment. In addition, our data confirmed erenumab effectiveness and safety in migraine prevention. Conclusion: Our study demonstrated an improvement in both subjective and objective sleep quality in patients treated with a migraine-preventive therapy. Erenumab, in particular, does not cross the blood brain barrier, thus a direct effect on sleep is unlikely. Future studies are needed to better understand the mutual influence between migraine and sleep disorders.